Prevalence of Gastrointestinal Disorders and Their Association With Stress and Sedentary Lifestyle in Working Professionals - Albadrani, Ahmed Abdullah; Al Abdulqader, Abdulrhman Khaled (Journal of Neonatal Surgery, 2025)
Background: Gastrointestinal (GI) disorders represent a significant health burden among working adults, yet the combined impact of occupational stress and sedentary behavior on symptom prevalence remains underexplored. Objectives: To determine the prevalence of GI disorders and to examine their associations with perceived stress and sedentary lifestyle in a cohort of working professionals in Saudi Arabia. Methods: In this descriptive, cross‑sectional study, 650 working professionals aged 20–60 years were recruited at King Fahad Hospital, Al‑Ahsa. Participants completed the Gastrointestinal Symptom Rating Scale (GSRS), the 10‑item Perceived Stress Scale (PSS‑10), and the Sedentary Behavior Questionnaire (SBQ). Descriptive statistics summarized sociodemographic data and scale scores. Pearson’s correlation coefficients assessed bivariate associations among GSRS, PSS‑10, and total sedentary time. Multiple linear regression models adjusted for age, gender, smoking status, and physical activity to identify independent predictors of overall GSRS score. Statistical significance was set at p < 0.05. Results: The mean total GSRS score was 15.5 ± 6.2, with 28% of participants reporting moderate‑to‑severe abdominal pain and 31% reporting moderate indigestion. The mean PSS‑10 score was 21.7 ± 6.1, and average daily sedentary time was 8.9 ± 2.3 hours. Perceived stress correlated strongly with total GSRS score (r = 0.52, p < 0.001), while sedentary time showed a moderate correlation (r = 0.25, p < 0.001). In multivariate analysis, both PSS‑10 score (β = 0.19, 95% CI: 0.13–0.27; p < 0.001) and sedentary time (β = 0.23, 95% CI: 0.09–0.37; p = 0.001) were independent predictors of GI symptom severity, accounting for 37% of the variance in GSRS scores. Conclusions: GI disorders are highly prevalent among working professionals and are significantly associated with occupational stress and sedentary lifestyle. Workplace interventions targeting stress reduction and reduced sitting time may mitigate GI symptom burden in this population.